2013
DOI: 10.1016/j.bbamcr.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

ORAI3 silencing alters cell proliferation and cell cycle progression via c-myc pathway in breast cancer cells

Abstract: Members of the Orai family are highly selective calcium ion channels that play an important role in store-operated calcium entry. Among the three known Orai isoforms, Orai3 has gained increased attention, notably for its emerging role in cancer. We recently demonstrated that Orai3 channels are over-expressed in breast cancer (BC) biopsies, and involved specifically in proliferation, cell cycle progression and survival of MCF-7 BC cells. Here, we investigate the downstream signaling mechanisms affected by Orai3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 37 publications
5
87
0
1
Order By: Relevance
“…In MCF-7 breast cancer cells, G1 phase progression and G1/S transition were shown to depend on the ORAI3 Ca 2þ -permeable channel that contributes to store-operated Ca 2þ entry (SOCE) in these cells [23,24]. It positively regulates the expression of cyclins (D1, E), CDK4 and 2, and suppresses cyclin-dependent kinase inhibitors (CDKIs) such, p21 and p53 by regulating the expression and the activity of c-myc [24,25].…”
Section: Ca 2þ Remodelling That Promotes Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…In MCF-7 breast cancer cells, G1 phase progression and G1/S transition were shown to depend on the ORAI3 Ca 2þ -permeable channel that contributes to store-operated Ca 2þ entry (SOCE) in these cells [23,24]. It positively regulates the expression of cyclins (D1, E), CDK4 and 2, and suppresses cyclin-dependent kinase inhibitors (CDKIs) such, p21 and p53 by regulating the expression and the activity of c-myc [24,25].…”
Section: Ca 2þ Remodelling That Promotes Proliferationmentioning
confidence: 99%
“…Indeed, it was shown that TRPV6 and ORAI3 not only promote proliferation, but also increase survival of PCa and breast cancer cells, respectively [19,20,24]. ORAI3-conferred survival of breast cancer cells involved Ca 2þ -dependent increase of c-Myc expression and activity resulting in the inhibition of pro-apoptotic Bax protein expression [24,25]. It was also demonstrated that higher levels of TRPA1 channel confer apoptosis resistance and promote survival of small cell lung carcinoma (SCLC) cells via TRPA1-mediated Ca 2þ entry leading to stimulation of ERK1/ 2 via Src [50].…”
Section: Ca 2þ Remodelling In Conferring Apoptosis Resistancementioning
confidence: 99%
“…23 A follow-up study by the same group reported a correlation between Orai3 and c-myc expression in tumor tissues and ER + MCF-7 cells and that Orai3 knockdown inhibits both expression and activity of the proto-oncogene c-myc, presumably through the MAP Kinase pathway. 24 The role of Orai3 in ER + breast cancer cell survival was confirmed by Pangburn et al using nanoparticle-mediated delivery of siRNA targeting Orai3. 64 These authors encapsulated siRNA targeting Orai3 in polymersomes and showed that these polymersomes were able to deliver siRNA to T47D cells and MCF10A cells ("normal" breast epithelial cells).…”
mentioning
confidence: 77%
“…1). There are reported instances where Orai3 was shown to encode SOCE in a subset of breast cancer cells, expressing the estrogen receptors [23][24][25][26] and in mature effector T cells, 27 but in general SOCE is mediated by Orai1 homomultimeric channels. In fact, in the absence of functional Orai1 channels, ectopically expressed Orai3 can only partially compensate for Orai1 in mediating SOCE in HEK 293 and human fibroblasts.…”
Section: Store-operated Ca 2+ Entry (Soce)mentioning
confidence: 99%
“…In regard to other ORAI proteins, another important role in cell proliferation is also mediated by ORAI3, which is overexpressed in different cancers such as breast and prostate cancers (23,24). As far as breast cancer is concerned, several groups established that G 1 progression and G 1 /S transition phases are dependent on ORAI3-mediated SOCE in estrogen expressing (ERϩ) cell lines (MCF7 cell line) (24,25,69), by positively regulating the expression of cyclins (D1, E), CDK4 and 2, and suppressing cyclin-dependent kinase inhibitors (CDKIs), such as p21 and p53, through regulating the expression and activity of c-myc (24,25). In addition, the downstream Ca 2ϩ effectors have been identified, as both NFAT activity and ERK1/2 phosphorylation were increased by ORAI3-dependent SOCE-activation in the MCF7 cell line (69).…”
Section: Sustaining Proliferative Signaling/evading Growth Suppressorsmentioning
confidence: 99%